Association of walking energetics with amyloid beta status: Findings from the Baltimore Longitudinal Study of Aging. Issue 1 (20th August 2021) - Dougherty, Ryan J.; Ramachandran, Janani; Liu, Fangyu; An, Yang; Wanigatunga, Amal A.; Tian, Qu; Bilgel, Murat; Simonsick, Eleanor M.; Ferrucci, Luigi; Resnick, Susan M.; Schrack, Jennifer A.
Abstract: Introduction: Higher energetic costs for mobility predict gait speed decline. Slow gait is linked to cognitive decline and Alzheimer's disease (AD). Whether the energetic cost of walking is linked to AD pathology is unknown. We investigated the cross‐sectional association between the energetic cost of walking, gait speed, and amyloid beta (Aβ) status (+/−) in older adults. Methods: One hundred forty‐nine cognitively normal adults (56% women, mean age 77.5 ± 8.4 years) completed customary‐paced walking assessments with indirect calorimetry and 11 C‐Pittsburgh compound B positron emission tomography. Logistic regression models examined associations adjusted for demographics, body composition, comorbid conditions, and apolipoprotein E ε4. Results: Each 0.01 mL/kg/m greater energy cost was associated with 18% higher odds of being Aβ+ (odds ratio [OR] = 1.18; 95% confidence interval [CI]: 1.04 to 1.34; P = .011). These findings were not observed when investigating gait speed (OR = 0.99; 95% CI: 0.97 to 1.01; P = .321). Discussion: High energetic cost of walking is linked to AD pathology and may be a potential target for therapeutic intervention.